If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 32 = 28y + 0 Reorder the terms: 32 = 0 + 28y Remove the zero: 32 = 28y Solving 32 = 28y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-28y' to each side of the equation. 32 + -28y = 28y + -28y Combine like terms: 28y + -28y = 0 32 + -28y = 0 Add '-32' to each side of the equation. 32 + -32 + -28y = 0 + -32 Combine like terms: 32 + -32 = 0 0 + -28y = 0 + -32 -28y = 0 + -32 Combine like terms: 0 + -32 = -32 -28y = -32 Divide each side by '-28'. y = 1.142857143 Simplifying y = 1.142857143
| 12t^3-9t^2+28t=3t^2(4t-3)+7(4t-3) | | 13x+42=4x+5 | | 6y+1.5x=8 | | 2(x-3)+2=4(x+6)-30 | | -2+2p=-14 | | 13y+(4y)(3x)+x= | | 5x+15=15-3x+9 | | 4y-6=-22 | | 2(x-4)+3=4x+7 | | 6x^2+47x+92=0 | | (2x+28)=(3x+137) | | -24-7n=-8(3-6n) | | 42=3(2-3n)-6 | | -19=3(7+3n)+8(8n-5) | | 180=111-u | | -12+19/-7= | | -12+-42/-7= | | 60x^2-20x+1=0 | | 84=2w+2L-3 | | 15y-11y=20 | | -12+-126/-7= | | x^2+(x*y)=120 | | 84+3x=1x | | -9u-5+6=19 | | -12+h/7=6 | | -a+5+6a=1+5a+3 | | -12+h/7= | | 8x+4(2-3x)=36-6x | | (4x-3)+3(3x+6)=5x-1 | | 4x^3-33x^2-30x=0 | | 2x+17+3x-4=180 | | 32=2x+14 |